Prison sentences: last resort or the default sanction? - Castro-Rodrigues, Andreia (2019)
This paper discusses the sentencing purposes for penal penalties, judges’ perceptions of sentencing purposes and prison sentences, and the effects of penal sanctions. We examine judges’ positions towards different penalties, with a focus on imprisonment, since their views on the different penalties are related to their sentencing decision-making. Understanding these views is then critical for several practical and political purposes, including bridging the gap between academic discourse and legal practice. We accessed judges’ views on penal sanctions through a questionnaire and an interview. Our sample is compounded by the judges of the criminal courts from the three major cities in Portugal. Despite the most recent criminological empirical knowledge, judges valued imprisonment as the most adequate sentence, both for different crimes and for different judicial purposes. This result is not consistent with viewing imprisonment as a ‘last resort’ solution. Indeed, we did not find this ‘last resort’ position in our data, and it is not apparent in the judicial statistics on imprisonment rates. Our data highlight the importance of increasing judges’ training on criminological and sociological issues as well as the importance of changing the influence of their personal beliefs regarding penal sanctions into research-based positions.